Six‐year follow‐up of vitiligo patients successfully treated with autologous non‐cultured melanocyte–keratinocyte transplantation. (22nd February 2019) - Altalhab, S.; AlJasser, M.I.; Mulekar, S.V.; Al Issa, A.; Mulekar, S.; Diaz, J.; Diallo, A.; Ezzedine, K.
Abstract: Background: Although autologous non‐cultured melanocyte–keratinocyte transplantation is a treatment option for stable vitiligo, there is lack of long‐term maintenance data for this specific treatment. Objective: To search for factors associated with long‐term maintenance of patients with stable vitiligo successfully treated with melanocyte–keratinocyte transplantation. Methods: This was a single‐centre retrospective study including stable vitiligo patients who underwent successful melanocyte–keratinocyte transplantation in the National Center for Vitiligo, Riyadh, Saudi Arabia, between 1 January 2004 and 30 June 2015. Cox proportional hazard model was used to estimate factors associated with relapse at 6 years of followup. Co‐variates included, gender, type of vitiligo, age at vitiligo onset, age at surgical procedure, disease duration, disease stability, affected body surface area, treated surface area, fingertip involvement, type of recipient area treatment and recurrence defined as the onset of new lesions on previously untreated areas. The risk of developing relapse defined as re‐appearance of more than 10% depigmentation in a previously treated and repigmented site was considered as the main outcome. Results: In total, 602 patients were included in the study of whom 410 (67%) were women. Mean age was 24.25 years [4.0–67.0]. Affected body surface area of less than 1% (adjusted HR = 0.37; P = 0.04) and mechanical dermabrasion (adjusted HR = 0.26; P = 0.03) were independently associated with lower rates of relapse. On the contrary, non‐segmental type of vitiligo (adjusted HR = 2.11; P = 0.03) and fingertip involvement (adjusted HR = 3.75; P = 0.01) were independently associated with higher rates of relapse. Conclusions: Criteria for selecting patients with stable vitiligo for surgery should include careful assessment of vitiligo type including body surface area of vitiligo and involvement of fingertip before undergoing surgical procedure.